EFFECT OF MANURE PLUS AND INORGANIC FERTILIZER ON MAIZE PRODUCTION AND NUTRIENT UPTAKE IN CENTRAL JAVA INDONESIA (Proceedings of the International Conference on Agriculture, 2018)
Maize is used by farmer under crop-livestock integrated farming system (CLIFS) in Indonesia. The characteristic of CLIFS is crop yield for food, stover for feed, cattle dung for manure as organic fertilizer. The quality of manure could be increased by adding organic phosphorus (guano, rock phosphate/RP) at initial phase of decomposition process. This research was aimed to improve manure quality by adding organic P (RP, guano) that was called as manure plus, then to evaluate manure plus and inorganic fertilizer on maize production, dry matter (DM) production and nutrient uptake of stover. Chemical properties of manure, manure plus and nutrient of stover were evaluated at the laboratory and field experiment with 6 treatments of fertilization and five replicates at latosolic soil. The treatments were (TSP+SA+KCl), manure+ (TSP+SA+KCl), manure+ (RP+SA+KCl), manure+  (guano+SA+KCl), (RP-manure)+ SA+KCl and (guano-manure)+ SA+KCl. The maize was harvested at 11 weeks after planting. Parameter measured were maize production, DM production and nutrient uptake of stover. The result showed that the chemical properties of manure plus was varied. RP-manure was higher in P (3.26%) and K (3.10%) compared to manure and guano-manure. Guano-manure was higher in N (1.66%) compared to manure and RP-manure. However, the effect of all the treatment was no significantly different on maize production, DM production and nutrient uptake of stover, except on N uptake of stover. It was concluded that manure plus replaces TSP as inorganic fertilizer.
Keywords: Guano; manure; nutrient; rock phosphate; waxy-corn